Differences in maturity pattern between mandibular posterior teeth and sagittal skeletal malocclusion - Shinta Amini Prativi; Ria Noor Firman; Belly Sam; Avi Laviana (Majalah Kedokteran Gigi Indonesia, 2020)
The availability of X-rays in dentistry may help visualize the stage of development of dental maturity. The high prevalence of malocclusion in a population and contradictory research results on dental maturation in each skeletal malocclusion encourage the authors to know the maturity pattern of the posterior mandibular teeth in each skeletal relation and the difference in women and men. A cross-sectional study was conducted with a sample size of 214 panoramic and cephalometric radiographs from skeletal malocclusion patients based on ANB angle (class I: 73, class II: 75, class III: 56) with an age ranging from 8 to16 years old. Maturation of the second premolar and second molar was assessed using Demirjian method. Statistical analysis used the non-parametric Kruskal Wallis test to show the difference in maturity patterns in each class of skeletal relations and Mann Whitney test to show the difference in females’ and males’ maturity patterns. There were significant differences in females and males dental maturity patterns in which female dental maturation was advanced than male. Differences in each skeletal relationare not significant.